2007
DOI: 10.1016/j.jbiotec.2007.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of secretory β1,3-N-acetylglucosaminyltransferase 2 fusion protein into hemolymph of Bombyx mori larvae using recombinant BmNPV bacmid integrated signal sequence

Abstract: The enhanced secretion of beta1,3-N-acetylglucosaminyltransferase 2 (beta3GnT2) fusion protein into the hemolymph of Bombyx mori larvae was studied using a recombinant B. mori nucleopolyhedrovirus (BmNPV) bacmid integrating seven signal sequences. When the BmNPV bacmid encoding the signal sequences from the silkworm B. mori bombyxin (bx) and B. mori prophenoloxidase-activating enzyme (ppae) was injected into silkworm larvae, 56.1 and 51.5mU/ml beta3GnT, respectively, were secreted into the hemolymph of silkwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In a previous study, we confirmed that the bx signal peptide allowed recombinant proteins to be secreted into culture supernatants of Bm5 cells, and into the hemolymph of silkworm larvae, but the gp signal peptide did not [10]. Therefore, the bx signal peptide was adopted for silkworm larvae expression.…”
Section: Expression Of Human A4gnt In Silkworm Larvaementioning
confidence: 81%
See 2 more Smart Citations
“…In a previous study, we confirmed that the bx signal peptide allowed recombinant proteins to be secreted into culture supernatants of Bm5 cells, and into the hemolymph of silkworm larvae, but the gp signal peptide did not [10]. Therefore, the bx signal peptide was adopted for silkworm larvae expression.…”
Section: Expression Of Human A4gnt In Silkworm Larvaementioning
confidence: 81%
“…1b), indicating that a4GnT productivity of Tn-pXgp/GFP uv -a4GnT in cell line 5 was higher than that in cell line 3. A previous report found that a GFP uvb3GnT2 fusion protein was not secreted by the gp signal peptide in Bm5 cells isolated from B. mori ovaries [10]. This indicates that the bx signal peptide may not be functional in Tn-5B1-4 cells, but Bm5 cells, because bx signal peptide is from bombyxin of silkworm.…”
Section: Expression Of Human A4gnt In Stable Insect Cell Linesmentioning
confidence: 90%
See 1 more Smart Citation
“…This was also shown when using BmNPV bacmids containing a viral protease: more than 90% of total protein was detected in the hemolymph of silkworm larvae. 28 However, the secreted proteins appear to be especially susceptible to intracellular aggregation because of the complexity of the secretion pathway. It has been reported that secreted levels of expressed protein can be 10 to 100 times lower than intracellular levels.…”
Section: Discussionmentioning
confidence: 99%
“…130 kbp, which is much larger than that of plasmid vectors; the transfection of large DNA such as the BmNPV bacmid has not previously been conducted. To confirm the transfection efficiency, GFP uv -b1,3-N-acetylglucosaminyltransferase 2 (b3GnT2) fusion protein (GGT2) was expressed in Bm5 cells and silkworm larvae (Park et al 2007) using the chitosan/BmNPV bacmid DNA nanocomplexes. To demonstrate the versatility of these chitosan-based nanocomplexes, rat a2,6-sialyltransferase (ST6), hemagglutinin (HA) from an influenza A virus, and the Neospora caninum surface protein (NcSRS2) were expressed using the chitosan/BmNPV bacmid DNA nanocomplexes.…”
mentioning
confidence: 99%